2017
DOI: 10.1002/ange.201611536
|View full text |Cite
|
Sign up to set email alerts
|

Katalytische Friedel‐Crafts‐C‐H‐Borylierung elektronenreicher Arene: starke Reaktionsbeschleunigung durch Versetzen mit Alkenen

Abstract: Bei einer elektrophilen C-H-Borylierung elektronenreicher Arene mit Catecholboran wird die katalytische Bildung des Borelektrophils durch B-H-Bindungsheterolyse mit verschiedenen Lewis-und Brønsted-Säuren eingeleitet. Dabei bildet sich nur das Boroniumion. NachD issoziation eines Liganden geht das dazugehçrige Boreniumion regioselektive elektrophile aromatische Substitutionen mit Anilinderivaten und N-Heterocyclen ein. Die Katalyse ist fürB(C 6 F 5 ) 3 als Initiator optimiert und läuft ohne Zusatz einer extern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 69 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…[12] In 2010, Ingleson and co‐workers reported the first transition metal‐free catalytic C−H borylation of alkyl aromatics with HBcat employing in situ generated [catB][CbBr 6 ] (CbBr 6 = closo ‐1‐H‐CB 11 H 5 Br 6 ) as a catalyst (Scheme 2a) [13] . In continuation of their studies on ruthenium(II) thiolate complex catalyzed aromatic C−H borylation, [14] Oestreich and co‐workers achieved a B(C 6 F 5 ) 3 ‐catalyzed C−H borylation of electron‐rich arenes (anilines, indoles and pyrroles) with HBcat (Scheme 2b) [15] . Mechanistic studies revealed a classical S E Ar mechanism involving boronium/borenium ions as reactive intermediates.…”
Section: Aromatic C−h Borylationmentioning
confidence: 97%
“…[12] In 2010, Ingleson and co‐workers reported the first transition metal‐free catalytic C−H borylation of alkyl aromatics with HBcat employing in situ generated [catB][CbBr 6 ] (CbBr 6 = closo ‐1‐H‐CB 11 H 5 Br 6 ) as a catalyst (Scheme 2a) [13] . In continuation of their studies on ruthenium(II) thiolate complex catalyzed aromatic C−H borylation, [14] Oestreich and co‐workers achieved a B(C 6 F 5 ) 3 ‐catalyzed C−H borylation of electron‐rich arenes (anilines, indoles and pyrroles) with HBcat (Scheme 2b) [15] . Mechanistic studies revealed a classical S E Ar mechanism involving boronium/borenium ions as reactive intermediates.…”
Section: Aromatic C−h Borylationmentioning
confidence: 97%
“…Although a catalytic version was reported by Ingleson and co‐workers, who used [Et 3 Si][HCB 11 H 5 Br 6 ] as a catalyst, [38] only limited progress was made until the discovery that B(C 6 F 5 ) 3 can be used as an efficient catalyst for the same purpose. In 2017, Oestreich and co‐workers reported that B(C 6 F 5 ) 3 alone acts as an initiator for activating the hydrogen–boron bond in hydroborane derivatives and facilitates C−H borylation through the formation of reactive boron electrophiles (Scheme 7a) [48] . Typically, the reaction took place selectively at electron‐rich positions of (hetero)arene systems.…”
Section: Selective C−h Borylation Controlled By Electronic Effectsmentioning
confidence: 99%
“…In light of the popularity of this transformation, there is a sustained interest in developing methodologies to form organoboron reagents. Three main pathways are used to prepare borylated thiophenes: metalation, [6,21] transition‐metal catalyzed borylation [22–27] and electrophilic borylation (Scheme 1A−B) [28–31] . Direct C−H activation is usually performed through Ir catalysis, allowing efficient and mild borylation conditions [23] .…”
Section: Introductionmentioning
confidence: 99%